Phylogenetic Analyses Suggest that Factors Other Than the Capsid Protein Play a Role in the Epidemic Potential of GII.2 Norovirus - Kentaro Tohma (American Society for Microbiology, 2017)
ABSTRACT Norovirus is the leading cause of acute gastroenteritis worldwide. For over two decades, a single genotype (GII.4) has been responsible for most norovirus-associated cases. However, during the winter of 2014 to 2015, the GII.4 strains were displaced by a rarely detected genotype (GII.17) in several countries of the Asian continent. Moreover, during the winter of 2016 to 2017, the GII.2 strain reemerged as predominant in different countries worldwide. This reemerging GII.2 strain is a recombinant virus that presents a GII.P16 polymerase genotype. In this study, we investigated the evolutionary dynamics of GII.2 to determine the mechanism of this sudden emergence in the human population. The phylogenetic analyses indicated strong linear evolution of the VP1-encoding sequence, albeit with minor changes in the amino acid sequence over time. Without major genetic differences among the strains, a clustering based on the polymerase genotype was observed in the tree. This association did not affect the substitution rate of the VP1. Phylogenetic analyses of the polymerase region showed that reemerging GII.P16-GII.2 strains diverged into a new cluster, with a small number of amino acid substitutions detected on the surface of the associated polymerase. Thus, besides recombination or antigenic shift, point mutations in nonstructural proteins could also lead to novel properties with epidemic potential in different norovirus genotypes. IMPORTANCE Noroviruses are a major cause of gastroenteritis worldwide. Currently, there is no vaccine or specific antiviral available to treat norovirus disease. Multiple norovirus strains infect humans, but a single genotype (GII.4) has been regarded as the most important cause of viral gastroenteritis outbreaks worldwide. Its persistence and predominance have been explained by the continuous replacement of variants that present new antigenic properties on their capsid protein, thus evading the herd immunity acquired to the previous variants. Over the last three seasons, minor genotypes have displaced the GII.4 viruses as the predominant strains. One of these genotypes, GII.2, reemerged as predominant during 2016 to 2017. Here we show that factors such as minor changes in the polymerase may have driven the reemergence of GII.2 during the last season. A better understanding of norovirus diversity is important for the development of effective treatments against noroviruses.